KONDISI LINGKUNGAN FISIK RUMAH TERHADAP KEJADIAN TUBERKULOSIS PARU DEWASA DI KABUPATEN BARITO KUALA - , HUMAINI; , Prof. Dr. dr. Adi Heru Sutomo. M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Pulmonary tuberculosis is a disease which is a serious issue. Based on reports from the Department of Health Barito Kuala district that the increase in cases of pulmonary tuberculosis from year to year, although there was a decrease in 2009, it can be seen from Case Detection Rate (CDR) in 2008 was 54.11%, in 2009 amounted to 52.11%, in 2010 recorded 58.44%, and 61.87% in 2011. Tuberculosis is caused by multiple risk factors, among others is factors of physical environmental of house with incidence of pulmonary tuberculosis AFB (Acid-Fast Bacilli) Positive among adults in Barito Kuala district. Objective: This study aims to identify the relationshipbetween theeffect of physical environment of houses to the incidence of pulmonary tuberculosis among adult in Barito Kuala District. Method: This study is an observational research with case control study design which examines the relationship between the specific effect (disease) to a particular risk factor. The number of samples in this study were 77 patients with tuberculosis AFB ( Acid-Fast Bacilli) positive as cases, and 77 controls (not tuberculosis). Data were analyzed by univariable statistical test, with chi square bivariate and multivariable logistic regression. Result: Results showed that the area of ventilation and lighting at homes correlate significantly with incidence of adult pulmonary tuberculosis in Barito Kuala District, while residential density, humidity, type of floor and wall conditions is not significantly associated. Conclusion: The most dominant risk factors with the incidence of adult pulmonary tuberculosis in Barito Kuala district, the lighting in homes that do not meet health requirements with adult pulmonary tuberculosis incidence.